2014
DOI: 10.1017/s1368980014001219
|View full text |Cite
|
Sign up to set email alerts
|

Family sociodemographic characteristics as correlates of children’s breakfast habits and weight status in eight European countries. The ENERGY (EuropeaN Energy balance Research to prevent excessive weight Gain among Youth) project

Abstract: Objective: The purpose of the present study was to investigate the associations of family sociodemographic characteristics with children's weight status and whether these potential associations are mediated by children's breakfast habits. Design: A school-based survey among 10-12-year-old children was conducted in eight European countries. Children's weight and height were measured and breakfast habits and family sociodemographic characteristics were self-reported by 5444 children and their parents. Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 51 publications
6
43
1
1
Order By: Relevance
“…The prevalence of skipping breakfast was lower than in other international studies using national data [9,10,23] with only 10% of children skipping breakfast at least once. This could be explained by the young age of our cohort, as skipping breakfast has been shown to increase with age [9,24] and previous studies included older children (aged 9-14 years old).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The prevalence of skipping breakfast was lower than in other international studies using national data [9,10,23] with only 10% of children skipping breakfast at least once. This could be explained by the young age of our cohort, as skipping breakfast has been shown to increase with age [9,24] and previous studies included older children (aged 9-14 years old).…”
Section: Discussioncontrasting
confidence: 68%
“…Short questions referring to breakfast consumption on the current day (as used here) are less prone to recall bias but may not capture usual eating patterns. Other studies have used a meal identified as breakfast in a 24-h recall [9]; eating or drinking something at home before school [10]; and eating within 2 hours of getting up [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a positive association between breakfast skipping and overweight in both genders [6,13,37,40,41,49,50]. In addition, a significant dose-response relationship between breakfast skipping and overweight was observed in Indian adolescents [37].…”
Section: Discussionmentioning
confidence: 94%
“…Omitting breakfast can lead to lower postprandial energy expenditure and contribute to changes in Another aspect that may interfere in the association between breakfast consumption and metabolic disorders is the quality of food consumed at breakfast, as whole foods rich in fiber promote satiety. Moreover, the intake of foods that contain high concentrations of refined carbohydrates and simple sugars at breakfast, or even breakfast skipping, can result in increased consumption of foods with high energy density at subsequent meals, contributing to weight gain [3,49,51]. This study was limited by a crosssectional design that does not allow inference of causality between observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…Dijkstra et al (17) found that taste preference mediated the association between income and adherence to the Dutch dietary guidelines for fruit, while the perception that fish is expensive mediated the association between income and meeting guidelines for fish consumption. Ahmadi et al (14) observed that socio-economic differences in daily vegetable intake among Canadian schoolaged children were mediated by parental norms; and Manios et al (15) found that the relationship between childhood SEP and overweight/obesity was mediated by daily breakfast consumption.…”
Section: Explanations For Socio-economic Inequalities In Diet and Bodmentioning
confidence: 99%